Racial diversity, immigrants and the well-being of residents: Evidence from U.S. counties - Masanori Kuroki (Global Labor Organization (GLO), 2017)
This paper presents empirical evidence that racial diversity and immigrant population at the local level tend to be associated with lower life satisfaction for Whites by matching individual data with the county-level population data during the period 2005-2010. The magnitudes I find suggest that a ten percentage-point increase in the share of the non-White population (approximately one-half of a standard deviation) is associated with 0.006 and 0.007 points reduction in life satisfaction on a four-point scale for White men and White women, respectively. For White men, this effect appears to be driven by the percentage of the population that is Black. I also find that a ten percentage-point increase in the percentage of the immigrant population (approximately two standard deviations) is associated with 0.009 and 0.021 points reduction in life satisfaction for White men and White women, respectively. The percentage of the non-White population seems to reduce older Whites' life satisfaction more than that of younger Whites. Though the scale of the findings relating to the impact of local racial compositions and immigrant population is relatively modest, the findings may pose a challenge in the coming years as the percentage of the population that is non-White rises in the United States.
Keywords: J15; I31; 330; life satisfaction; happiness; well-being; racial; immigration